2019
DOI: 10.2147/ndt.s197879
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dopaminergic pathway and primary visual cortex are involved in the freezing of gait in Parkinson’s disease: a PET-CT study</p>

Abstract: Background: Freezing of gait (FOG) could be partly alleviated by dopaminergic drugs but the mechanism still needs to be elucidated. The purpose of this study is to explore the mechanisms of FOG by vesicular monoamine transporter VMAT2 distribution with the 18 F-AV133 tracer and 18-fludeoxyglucose positron emission tomography–computed tomography ( 18 F-FDG PET-CT). Methods: Clinical material and PET-CT data were collected from 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Moreover, previous neuroimaging experiments have also implicated the visual cortex may be involved in the occurrence of FOG. Besides impaired functional connectivity in the visual cortex [8,11], one recent neurometabolic study using glucose positron emission tomography (PET) further supported that PD patients with FOG had lower metabolic activity in the visual cortex compared with those without FOG [41]. In particular, one virtual reality task-based fMRI study demonstrated that PD patients with FOG had increased visual cortex activation during turning, implicating that PD patients with FOG were over-reliant on visual information [42].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, previous neuroimaging experiments have also implicated the visual cortex may be involved in the occurrence of FOG. Besides impaired functional connectivity in the visual cortex [8,11], one recent neurometabolic study using glucose positron emission tomography (PET) further supported that PD patients with FOG had lower metabolic activity in the visual cortex compared with those without FOG [41]. In particular, one virtual reality task-based fMRI study demonstrated that PD patients with FOG had increased visual cortex activation during turning, implicating that PD patients with FOG were over-reliant on visual information [42].…”
Section: Discussionmentioning
confidence: 96%
“…The typical FOG symptom usually lasts for a few seconds, but occasionally can last for 30 s or more ( 6 ). Unlike other cardinal symptoms, FOG cannot be satisfactorily managed by dopaminergic medication or deep brain stimulation ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence has supported that resting state functional connectivity within the visual network decreased in PD-FOG patients (Tessitore et al, 2012;Canu et al, 2015). Moreover, Zhou et al (2019) observed significant decrease of the metabolism of the primary visual cortex using PET-CT in PD-FOG group compared with PD-NFOG (Zhou et al, 2019). It has been postulated that hypoactivation in visual brain area might underlie the deficits of visual network related to gait disturbances.…”
Section: Discussionmentioning
confidence: 97%